Vacuum-Formed Retainers Versus Lingual-Bonded Retainers: A Systematic Review and Meta-Analysis of Stability of Treatment Outcomes in Orthodontically Treated Patients - Seerab Husain; Shantha Sundari; Ravindra Kumar Jain; Arthi Balasubramaniam (Galenos Yayinevi, 2022)
Objective:This review aimed at analyzing the literature comparing vacuum-formed retainers and lingual-bonded retainers for maintaining treatment stability and periodontal health and evaluating retainer failure and patient satisfaction.Methods:Electronic databases such as PubMed, Cochrane Library, Ovid, Scopus, Web of Science, and Google Scholar were searched. Only randomized controlled trials were involved. Risk of bias was evaluated using Risk of Bias 2 Tool. Meta-analysis was performed and certainty of evidence was assessed with Grading of Recommendations Assessment, Development, and Evaluation approach.Results:Five randomized controlled trials were included for qualitative analysis and 2 studies were included for quantitative analysis. Two studies concluded that lingual-bonded retainers were more effective than vacuum-formed retainers in maintaining treatment stability. Two studies had a high risk of bias and 3 studies had some concerns. No statistically significant difference in Little's Irregularity Index (standard mean difference = −0.10; P value = .61), inter-canine width (standard mean difference = 0.66; P value = .09), inter-molar width (standard mean difference = 0.08; P value = .85), arch length (standard mean difference = −0.18; P value = .60) between the 2 retainers was noted. Periodontal status and retainer failure rate (odds ratio= 2.28; P value = .23) were similar in both retainers. Patient discomfort, soreness, and speech difficulty were more with vacuum-formed retainers and oral hygiene maintenance was easier with vacuum-formed retainers.Conclusion:A very low-level certainty of evidence suggests that both vacuum-formed retainers and lingual-bonded retainers were equally effective in maintaining treatment stability. Periodontal status and retainer failures were similar in both retainers. Vacuum- formed retainers were better for oral hygiene maintenance but were associated with discomfort, soreness, and speech difficulty than lingual-bonded retainers.